2012
DOI: 10.15288/jsad.2012.73.549
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder Symptoms Mediate the Relationship Between Traumatic Experiences and Drinking Behavior Among Women Attending Alcohol Serving Venues in a South African Township

Abstract: ABSTRACT. Objective: South Africa has high rates of traumatic experiences and alcohol abuse or dependence, especially among women. Traumatic experiences often result in symptoms of posttraumatic stress disorder (PTSD), and PTSD has been associated with hazardous drinking. This article examines the relationship between traumatic events and hazardous drinking among women who patronized alcohol-serving venues in South Africa and examines PTSD as a mediator of this relationship. Method: A total of 560 women were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…It is estimated that one-quarter to one-half of South African women have experienced a lifetime history of physical or sexual assault from a male partner (3-5), and in one study, one in ten experienced sexual assault from a non-partner (5). Because interpersonal violence is often co-occuring (4, 6) and may have a cumulative and interactive effect (7), it can be difficult to determine the independent effects of sexual violence. Experiences of interpersonal violence, and sexual trauma in particular, often result in traumatic stress symptoms, which affect cognitive, behavioral, and emotional functioning (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that one-quarter to one-half of South African women have experienced a lifetime history of physical or sexual assault from a male partner (3-5), and in one study, one in ten experienced sexual assault from a non-partner (5). Because interpersonal violence is often co-occuring (4, 6) and may have a cumulative and interactive effect (7), it can be difficult to determine the independent effects of sexual violence. Experiences of interpersonal violence, and sexual trauma in particular, often result in traumatic stress symptoms, which affect cognitive, behavioral, and emotional functioning (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…The study sampling and recruitment procedures have been described in detail previously. 9,27,29 In brief, 12 venues were selected for inclusion in the study, ranging in size (licensed taverns and unlicensed shebeens ), geographic distribution in the township, and ethnic diversity with some venues predominantly attended by Coloured (a recognized South African ethnic group of mixed-race ancestry) or by Black African patrons. From the 12 venues, female patrons were eligible if they attended the venue regularly, were at least 18 years old and lived in the study township.…”
Section: Methodsmentioning
confidence: 99%
“…26 In addition, traumatic experiences and stress symptoms are associated with increased alcohol use. 27 Therefore, women may try to cope with the traumatic stress by turning to alcohol as a form of self-medication. 28 …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, among a sample of female civilians and veterans with comorbid PTSD and alcohol dependence, Lehavot and colleagues (2013) found that reasons for drinking related to reducing negative affect were associated with amount of alcohol consumed on a typical occasion. This “self-medication hypothesis” also yielded support in samples of female survivors of intimate partner violence (IPV; e.g., sexual assault, domestic violence) (Kaysen et al, 2007; Watt et al, 2012) and adolescents (Dixon et al, 2009). …”
mentioning
confidence: 88%